Adsorption Kinetic Behaviour of Pure CO, N and CH in Natural Clinoptilolite at Different Temperatures - Gelacio Aguilar-Armenta; María E. Patiño-Iglesias; Roberto Leyva-Ramos (Adsorption Science & Technology)
The adsorption kinetics of pure CO 2 , N 2 and CH 4 on a natural clinoptilolite (ZSL) sample from Villa de Reyes (San Luis Potosí, México) were measured at different temperatures using a glass, high-vacuum volumetric system. The ability of the natural zeolite to adsorb these gases depended on the gas–adsorbent contact time, t. For short values of t, the gas adsorption uptakes decreased in the order CO 2 >> N 2 > CH 4 . However, for long t values, the adsorption uptakes decreased in the sequence CO 2 > CH 4 > N 2 . It was established that the activation energies (kJ/mol) for the adsorption process increased in the following order CO 2 (15) < N 2 (18) < CH 4 (40), correlating fairly well with the increasing order of kinetic diameter (Å) of the molecules: CO 2 (3.3) < N 2 (3.64) < CH 4 (3.8). In comparison to the ZSL sample, the rate of adsorption of N 2 and CH 4 on H-ZSL increased and the total adsorption capacity decreased. The ZSL sample may be recommended as an effective adsorbent for the separation of CO 2 /CH 4 and N 2 /CH 4 mixtures.